2013
DOI: 10.1186/1556-276x-8-96
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the killing effects between nitrogen-doped and pure TiO2 on HeLa cells with visible light irradiation

Abstract: The killing effect of nitrogen-doped titanium dioxide (N-TiO2) nanoparticles on human cervical carcinoma (HeLa) cells by visible light photodynamic therapy (PDT) was higher than that of TiO2 nanoparticles. To study the mechanism of the killing effect, the reactive oxygen species produced by the visible-light-activated N-TiO2 and pure-TiO2 were evaluated and compared. The changes of the cellular parameters, such as the mitochondrial membrane potential (MMP), intracellular Ca2+, and nitrogen monoxide (NO) concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 36 publications
(38 reference statements)
2
24
0
Order By: Relevance
“…There was a significant change in ROS production between ambient and blue light treatments after exposure to the highest dosage (200 μg/mL) of N-TiO 2 NPs. Although there are relatively few investigations which report on ROS production of N-TiO 2 NPs in mammalian cell models, our ROS results match those described in Li et al's report, 48 which compared the cytotoxicity of undoped and N-doped TiO 2 NPs in HeLa cells. In the aforementioned studies, irradiation with blue light (400-440 nm) for up to 5 minutes resulted in substantial increases in total ROS as well as superoxide and hydroxyl radical formation at similar concentrations to those used in our study.…”
Section: Biocompatibility and Antibacterial Activity Of N-tio 2 Npssupporting
confidence: 89%
See 1 more Smart Citation
“…There was a significant change in ROS production between ambient and blue light treatments after exposure to the highest dosage (200 μg/mL) of N-TiO 2 NPs. Although there are relatively few investigations which report on ROS production of N-TiO 2 NPs in mammalian cell models, our ROS results match those described in Li et al's report, 48 which compared the cytotoxicity of undoped and N-doped TiO 2 NPs in HeLa cells. In the aforementioned studies, irradiation with blue light (400-440 nm) for up to 5 minutes resulted in substantial increases in total ROS as well as superoxide and hydroxyl radical formation at similar concentrations to those used in our study.…”
Section: Biocompatibility and Antibacterial Activity Of N-tio 2 Npssupporting
confidence: 89%
“…Some reports agree with our finding that superoxide radicals are produced, 30,48 while others indicate that carbon-centered radicals are produced. 19 Nonetheless, the presence of free radicals indicates that cells may be exposed to conditions that promote oxidative stress, which could result in adverse cellular responses including cell death.…”
supporting
confidence: 91%
“…Preliminary tests in the laboratory demonstrated that the procedure is efficient and several improvements have already been suggested [11]. Nevertheless, such an approach can be used solely for few cancers, where the activation by visible of UV light is possible.…”
Section: Resultsmentioning
confidence: 99%
“…The production of ROS by semiconducting/conducting nanoparticle (such as TiO 2 ) and light in cell cultures (human cervical carcinoma cells HeLa) has been confirmed [11]. A study aiming directly at TiO 2 exposed to H 2 O 2 in ambient light and dark demonstrated that free oxygen containing radicals (ROS) could be generated in the absence of light if H 2 O 2 is present.…”
Section: Potential Biological and Medical Applicationsmentioning
confidence: 93%
See 1 more Smart Citation